PENINGKATAN HASIL BELAJAR IPS DENGAN METODE NUMBERED HEAD TOGETHER PADA SISWA KELAS IVA SDN 004 PINANG SERIBU SAMARINDA UTARA - Gamar Al Haddar; Nurul Hikmah; Serina Agung (PENDAS MAHAKAM: Jurnal Pendidikan dan Pembelajaran Sekolah Dasar, 2018)
This study aims to determine the increase in social studies learning outcomes with the Numbered Heads Together learning for IVA graders at SD 004 Pinang Seribu North Samarinda in 2016/2017.This type of research is classroom action research conducted at SDN 004 Pinang Seribu, North Samarinda. This Classroom Action Research carried out three cycles. Each cycle has three meetings. The research subjects were class IVA students, amounting to 30 people. The instruments used in this study were learning outcomes tests, student observation sheets, student interview sheets and documentation.Based on the results of the classroom action research that has been carried out it can be concluded that the application of Numbered heads together learning method can improve social studies learning outcomes, it can be seen in the first cycle in the medium category and not completed with an average score of 47% because the learning process has not been implemented Maximum in cycle II has increased with 97% completeness average in very good category, and in cycle III student learning outcomes reach 100% completeness average with very good category and have achieved minimum completeness value.